The extent to which geometry and measurement topics are identical in the fourth grade mathematics books (Scientific and literary) with standards close mathematics curriculum (Journal of the College of Basic Education, 2023)
Summary of the research:The current research aims to determine (the extent to which the subjects of geometry and measurement in the fourth mathematics book (scientific and literary) correspond to the standards of the mathematics curriculum document), and the researcher followed the descriptive analytical approach. (4) axes and (17) criteria, and its validity was confirmed by Al-Dahiri by presenting it to specialists in the methods of teaching mathematics and curricula. The research sample consisted of geometry and measurement topics included in mathematics books. The results of the research concluded that the availability of standards for the mathematics curriculum document in the subjects of engineering and measurement is unacceptable by (50.6%). Textbooks, paying attention to the standards that were not included and working to include them.Keywords: geometry and measurement topics, mathematics curriculum document standards